Relationship between Socio-Economic Status and New Word Learning - Abhishek B.P (International Journal of Education Sciences, 2024)
New word learning refers to the process of learning of novel words which are not in the vocabulary of the person and it varies as a function of many potent variables. Socio economic status is one of the major variables believed to have a significant effect on new word learning. The aim of the current study to investigate if new word learning varies as a function of socio-economic status. 74 children (studying in 1st and 2nd grade) were recruited. Children were taken from two different schools and in addition to this the NIMH scale was also administered to elicit details regarding socio economic status (SES). The NIMH and school data were used to categorize children into groups according to their SES. Thirty uncommon nouns were asked to be named by the participants. The starting point score for each participant was 0. The names were told to the participants and testing was repeated immediately, this phase was termed as training phase. The testing was also carried out after 3 days post training. Scores obtained on the third day was taken into consideration for statistical analysis as it would reflect new word learning. Mann Whitney U test was administered and the statistic revealed a significant difference between children belonging to higher and lower SES with children belonging to higher socio-economic status performing better. This difference could be because of the rehearsal strategies adapted by children or follow up with parents.
Keywords: Fast Mapping; New words; Socio Economic status; Strata; Vocabulary